The blossom and the firefly - Smith, Sherri L. (G.P. Putnam's Sons, 2020)
Suffering from the post-traumatic stress of being buried alive after a 1945 bombing raid on her Japanese hometown, fifteen-year-old Hana feels she has nothing to live for until meets seventeen-year-old Taro, a Kamikaze pilot training for his one and only mission. Over a period of eight days, Hana and Taro fall in love and await Taro's inevitable mission.